The influence of beam parameters on FLASH effect - Lin, Binwei; Du, Huan; Hao, Xiaofei; Liang, Yuwen; Xu, Haonan; Tang, Wenqiang; Li, Jie; Zhang, Yu; Du, Xiao Bo (Frontiers in Oncology, 2025)
Ultra-high dose rate radiotherapy (FLASH-RT) is typically defined as an external beam radiotherapy that utilizes a dose rate of 40 Gy/s or higher, compared with conventional dose rate radiotherapy (≤0.1 Gy/s). The primary advantage of FLASH-RT lies in its ability to minimize damage to organs at risk surrounding the cancer while preserving the anti-tumor effect. This phenomenon, known as the FLASH effect, has been widely studied in various bodily systems. However, recent publication of negative research findings related to FLASH-RT warrant a reassessment of whether this definition is accurate. Therefore, this review aims to critically examine how various beam parameters impact the manifestation of the FLASH effect. Following extensive literature review, we propose that an average dose rate of 40 Gy/s to be the lowest dose that triggers the FLASH effect. Beyond this threshold, different organs, including the brain, lungs, intestine, and skin, required varying minimum single total doses to trigger FLASH effects, with a trend of enhanced FLASH-RT protective effects as the single total doses increased. Moreover, single or multiple pulses and the characteristic parameters of the pulse structure, including single pulse dosage, pulse width, pulse interval, pulse frequency, and total irradiation time, were found to also impact the FLASH effect.